2009
DOI: 10.1016/j.brat.2009.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Managing unwanted intrusive thoughts in obsessive–compulsive disorder: Relative effectiveness of suppression, focused distraction, and acceptance

Abstract: Suppression is one of various mental control techniques that people may use to manage unwanted thoughts. Evidence suggests that it is at best unsustainable and at worst counterproductive. This leads to the question: If suppression is a futile way to respond to unwanted, intrusive, thoughts, what is a more effective alternative? In the current study, we evaluated the relative effectiveness of suppression and two alternative mental control techniques-focused distraction and acceptance-on the frequency of intrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 66 publications
7
84
0
4
Order By: Relevance
“…In seven studies, acceptance strategies were superior to suppression strategies (Campbell-Sills et al, 2006;Dunn et al, 2009;Liverant et al, 2008;Marcks & Woods, 2005;Masedo & Rosa Esteve, 2007;Najmi et al, 2009;. Five studies found no significant difference between acceptance and suppression strategies (Dunn et al, 2009;Feldner et al, 2003;Najmi et al, 2009;Westin et al, 2008).…”
Section: Superiority Of Acceptance Strategies To Suppression Distracmentioning
confidence: 89%
See 4 more Smart Citations
“…In seven studies, acceptance strategies were superior to suppression strategies (Campbell-Sills et al, 2006;Dunn et al, 2009;Liverant et al, 2008;Marcks & Woods, 2005;Masedo & Rosa Esteve, 2007;Najmi et al, 2009;. Five studies found no significant difference between acceptance and suppression strategies (Dunn et al, 2009;Feldner et al, 2003;Najmi et al, 2009;Westin et al, 2008).…”
Section: Superiority Of Acceptance Strategies To Suppression Distracmentioning
confidence: 89%
“…Seven studies did not find any significant differences between acceptance and distraction strategies Keogh et al, 2005;Kuehner et al, 2009;McMullen et al, 2008;Najmi et al, 2009;Singer & Dobson, 2007;Westin et al, 2008).…”
Section: Superiority Of Acceptance Strategies To Suppression Distracmentioning
confidence: 93%
See 3 more Smart Citations